Rivaroxaban for Thromboprophylaxis after Hospitalization for Medical Illness - Spyropoulos, Alex C; Ageno, Walter; Albers, Gregory W; Elliott, C Gregory; Halperin, Jonathan L; Hiatt, William R; Maynard, Gregory A; Steg, P Gabriel; Weitz, Jeffrey I; Suh, Eunyoung; Spiro, Theodore E; Barnathan, Elliot S; et al. (My University, 2018)
Patients who are hospitalized for medical illness remain at risk for venous thromboembolism after discharge, but the role of extended thromboprophylaxis in the treatment of such patients is a subject of controversy.